2017
DOI: 10.1371/journal.pone.0188742
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of WRKY gene family in Oryza officinalis Wall ex Watt and WRKY genes involved in responses to Xanthomonas oryzae pv. oryzae stress

Abstract: Oryza officinalis Wall ex Watt, a very important and special wild rice species, shows abundant genetic diversity and disease resistance features, especially high resistance to bacterial blight. The molecular mechanisms of bacterial blight resistance in O. officinalis have not yet been elucidated. The WRKY transcription factor family is one of the largest gene families involved in plant growth, development and stress response. However, little is known about the numbers, structure, molecular phylogenetics, and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…Group Ib includes CcWRKY25 and HaWRKY67 genes. Previous studies have reported the presence of group Ib in some monocotyledonous plants; for example, eight WRKY genes found in rice, six in O. officinalis Wall ex Watt, and one ( PheWRKY61 ) in moso bamboo [9,24,31]. The only WRKY genes in group Ib uncovered in our study were in globe artichoke and sunflower (all dicotyledonous plants).…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Group Ib includes CcWRKY25 and HaWRKY67 genes. Previous studies have reported the presence of group Ib in some monocotyledonous plants; for example, eight WRKY genes found in rice, six in O. officinalis Wall ex Watt, and one ( PheWRKY61 ) in moso bamboo [9,24,31]. The only WRKY genes in group Ib uncovered in our study were in globe artichoke and sunflower (all dicotyledonous plants).…”
Section: Discussionsupporting
confidence: 53%
“…Although CcWRKY25 and HaWRKY67 genes fell into group III in the phylogenetic tree, they contain two WRKY domains and thus belong to group I. Group Ib has arisen from group III via the duplication of WRKY genes [19]; this WRKY transcription factor’s evolutionary patterns has also been confirmed in wild rice [31]. Although PgWRKY42 and PgWRKY122 of ginseng cannot be classified into any of the three groups in the phylogenetic tree, they cluster with group I and may have originated through the loss of the WRKY domain during the course of evolution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Members in group II have a CX 5 CX 23 HXH zinc finger motif, except subgroup IIc, which has a CX 4 CX 23 HXH zinc finger that is the same as that in the C-terminal WD (CTWD) of group I WRKY proteins. The subgroup IIc members can be clustered into separated clades, in which the ancient IIc clade neighbors the CTWD clade (Xu et al 2016;Jiang et al 2017b), suggesting a close evolutionary relationship between genes in group I and subgroup IIc. Subgroup IIc has also been proposed to be a separate group by Zhang and Wang (2005) or subgroup Ib by Wu et al (2005).…”
Section: Wrky Structure and Evolutionmentioning
confidence: 99%
“…Subgroup IIc has also been proposed to be a separate group by Zhang and Wang (2005) or subgroup Ib by Wu et al (2005). In addition to variations in zinc finger motifs, mutations in the consensus WRKYGQK sequence often appear in various plant species, and frequently observed variants include WRKYGKK and WRKYGEK (Wu et al 2005;Yao et al 2015;Jiang et al 2017b;Yang et al 2017;Song et al 2018).…”
Section: Wrky Structure and Evolutionmentioning
confidence: 99%